Analisis Kebijakan Program PKBM dalam Meningkatkan Minat Belajar Bahasa Inggris di Program Paket B: Studi Kasus di PKBM Alam Medan (Journal Edutama Multidisciplinary Indonesian, 2024)
This study aims to analyze the policies and implementation of the Community Learning Center (PKBM) program in enhancing English learning interest within the Package B Program, with a case study at PKBM Alam Medan. Using a qualitative approach and case study method, data were collected through interviews, observations, and document analysis. The findings indicate that PKBM policy implementation faces various challenges, including low student interest in learning English. Factors such as students’ perceptions of English difficulty, lack of material relevance, less interactive teaching methods, and limited technology integration contribute to the low learning interest. PKBM Alam Medan has attempted to address these challenges through strategies such as the use of interactive media, project-based learning, and adjusting materials to local needs, although implementation remains constrained by limited resources and varied tutor competencies. This study highlights the need for a comprehensive approach and stakeholder support to optimize the role of PKBM as a nonformal education institution in Indonesia, especially for English learning in the globalization era.